Master actions for massive spin-3 particles in D = 2 + 1 - Mendonça, Elias Leite [UNESP]; Dalmazi, Denis [UNESP] (Springer Nature, 2016)
We present here a relationship between massive self-dual models for spin-3 particles in (Formula presented.) via the master action procedure. Starting with a first-order model (in the derivatives) (Formula presented.) we have constructed a master action which interpolates between a sequence of four self-dual models (Formula presented.) where (Formula presented.). By analyzing the particle content of the mixing terms, we give additional arguments that explain why it is apparently impossible to jump from the fourth-order model to a higher-order model. We have also analyzed similarities and differences between the fourth-order K-term in the spin-2 case and the analogous fourth-order term in the spin-3 context.